Perfil cognitivo asociado al trastorno por estrés postraumático en víctimas de violencia armada (2008)
ABSTRACT: to determine the cognitiveprofile associated to the posttraumatic stress disorder (PTSD) in victims of armed violence in the state of Chocó - Colombia. Participants: 40 adults (70% women and 30% men). The instruments used were: M.I.N.I, CCE-TP and EEC-M. Procedure: A comparative analysis between groups was made, distributed as follows: group 1: exposed to violence with PTSD, n=15, and group 2: exposed to violence without PTSD n=25. Findings: 37% of participants presented PTSD. Significant differences were found between groups, with higher punctuations in the mean in group 1 in schizoid beliefs (p=.007; means 11.5 vs. 7.83) and professional support (p=.003; means 20.5 vs. 12.7), and lower punctuations in narcissistic beliefs (p=.001; means 7.8 vs. 10.46), religion (p=.002; means 28.12 vs. 35.8) and expression coping difficulty (p=.034; means 13.6 vs. 15.5). Conclusions: the cognitive profile associated to PTSD was characterized by affective distancing from others, search for professional support, low self-esteem, minor strategies related with religion and inhibition in expressing coping difficulties.